PENDIDIKAN BERBASIS INKLUSI DI SEKOLAH DASAR: MANFAAT DAN TANTANGAN - Ignasius Putera Setiahati; Arita Marini; Linda Zakiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Inclusive education is education where all children, including those with special needs, receive the same educational opportunities as other students. The aim of this research is to determine the benefits of inclusive education and the challenges experienced by Catholic-based private elementary schools. The research method used is a qualitative-description method. Data collection methods are observation, interviews and documentation. Interviews were conducted with three principals and six teachers from private Catholic elementary schools that implement inclusive education. The data analysis technique uses a coding system by grouping similar points so that the main benefits and challenges are found. From the research results, it was found that there are many benefits or positive values in inclusive education, such as students understanding and respecting differences, promoting schools, building cooperation with people with different abilities, and preparing children to enter the real world. Meanwhile, the challenges are limited human resources, inadequate facilities and infrastructure, as well as stereotypical views towards disabilities. In conclusion, inclusive education has a lot of value and benefits for education, but there are still many challenges that private elementary schools must face. Therefore, inclusive education should continue to be implemented but must be well prepared and collaborate with all parties involved to achieve the goals.